PENERAPAN MODEL COOPERATIF LEARNING TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPAS MATERI KEKAYAAN BUDAYA INDONESIA DI KELAS IV SDN GELAM 2 - Indah Suci Hati, - (2023)
This research is motivated by the low learning outcomes of grade IV students in learning IPAS material for Indonesian cultural wealth. Caused by several problems, namely, students are less enthusiastic, lack motivation and encouragement, and students are passive in learning and teachers do not apply interesting and innovative learning models. This research was carried out to describe the application of the jigsaw type cooperative learning model to improve student learning outcomes in Indonesian cultural wealth material in grade IV SDN Gelam 2. This research uses a qualitative approach with the Kemmis and Taggart model class action research (PTK) method. The results of the study can be seen from the acquisition of student learning results at each stage, namely, the pre-school stage students obtained an average score of 62.36 with a percentage of completeness of 36%. In cycle 1, the average score obtained by students increased by 72.96 with a percentage of completion of 60%. In cycle 2, the average score obtained by students increased, namely 81.52 The results of this study show that 100%. there is an increase in student learning outcomes in learning IPAS Indonesian cultural wealth material after applying a jigsaw type cooperative learning model in grade IV SDN Gelam 2.